STRATEGI REKRUTMEN DAN SELEKSI GURU DALAM MENINGKATKAN MUTU PENDIDIKAN DI MTSN 2 EMPAT LAWANG - Sri Uswatun Hasanah; Zainal Berlian; Baharuddin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze teacher recruitment and selection strategies in improving educational quality at MTsN 2 Empat Lawang. This research used a qualitative descriptive approach. Data were collected through interviews, observations, and documentation. The results showed that teacher recruitment was carried out based on the school's needs by considering applicants’ qualifications and competencies. The selection process included administrative screening, interviews, and competency assessments. These strategies helped the school obtain qualified teachers who supported the improvement of learning quality and educational outcomes. Although there were some challenges, such as the limited number of qualified applicants, the school continuously improved its recruitment and selection process to obtain professional and competent educators.